Outer membrane protein A (OmpA) of extraintestinal pathogenic Escherichia coli - Daniel W. Nielsen (BMC Research Notes, 2020)
Abstract Objective Extraintestinal Pathogenic E. coli (ExPEC), are responsible for host diseases such as Neonatal Meningitis Escherichia coli (NMEC), the second-leading cause of neonatal bacterial meningitis, Avian Pathogenic E. coli (APEC), a cause of extraintestinal disease in poultry, and Uropathogenic E. coli (UPEC), the most common cause of urinary tract infections. Virulence factors associated with NMEC include outer membrane protein A (OmpA) and type I fimbriae (FimH), which also occur in APEC and UPEC. OmpA contributes to NMEC’s ability to cross the blood–brain barrier, persist in the bloodstream and has been identified as a potential vaccine target for ExPEC, however the protein has amino acid variants, which may influence virulence of strains or alter vaccine efficacy. Although OmpA is present in virtually all E. coli, differences in its amino acid residues have yet to be surveyed in ExPEC. Results Here the ompA gene (n = 399) from ExPEC collections were sequenced and translated in silico. Twenty-five different OmpA polymorphism patterns were identified. Seven polymorphism patterns were significantly associated with an ExPEC subpathotype, but chromosomal history most likely accounts for most differences found. The differences in OmpA protein sequences suggest that OmpA may influence variation in virulence and host specificity within ExPEC subpathotypes.